\(-2 \times -1\) = \(2\)
taking log to the base ten on both sides we get
log−2+log−1 = log2
−log21+log−1 = log2 SINCE log−a = −loga1
log−1 = log2+log21
this can be written as
log−1 = log22
log−1 = log1
this implies log−13 = log−12 since −13 = −1 AND −12 = 1
3 log−1 = 2 log−1
dividing by log -1 to the base ten on both sides,we get
3 = 2
3 = 1 + 1
sorry this is a wrong proof
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Note that the logarithm formula is −loga1=loga, not "SINCE log−a=−loga1" as you claimed.
Log in to reply
thanks for correcting my mistake
i appreicate ur attempt for doing this,i request u think more like this....... (eppadi da room pottu yosipeengaloooo...)-just for fun
but you're using a number system where 1 plus 1 DOES equal 2 to prove something that contradicts this system... so no.